Modern Java in action : Lambdas. streams, reactive and functional programming - Urma, Raoul-Gabriel; Fusco, Mario; Mycroft, Alan (Manning Publications, 2019)
Helping readers build on their existing Java language skills with the newest features and techniques, this book gives users new ways of thinking about programming and writing code that is easier to read and maintain. --